2019
DOI: 10.1002/cplu.201900318
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Protic Ionic Liquids (PILs) in Reactive Systems: Rational Selection of PILs for the Design of Green Synthesis Strategies for Allylic Amines and β‐Amino Esters

Abstract: The reactive behaviour of protic ionic liquids (PILs) has been shown to be governed not only by their chemical structures but also by their global compositions, which include the presence of free acids and bases at equilibrium with ionic pairs. Six PILs composed of primary, secondary, or tertiary alkyl ammonium cations with two couterions, nitrate or acetate, were tested in model reactions with unsaturated substrates. The free species that were naturally present in these liquids were identified by cyclic volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Interestingly, in some cases, the different solubility of molecular and ionic species in different environments may result in the formation of a biphasic PIL . Ionicity, which is usually defined as the degree of proton transfer of a PIL, not only affects the physicochemical properties of a PIL but also governs its suitable applications. The quantitative study on the ionicity of biphasic PILs can provide useful information on both phase and proton-transferring equilibria in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in some cases, the different solubility of molecular and ionic species in different environments may result in the formation of a biphasic PIL . Ionicity, which is usually defined as the degree of proton transfer of a PIL, not only affects the physicochemical properties of a PIL but also governs its suitable applications. The quantitative study on the ionicity of biphasic PILs can provide useful information on both phase and proton-transferring equilibria in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was recently reported that alkylammonium-derived ILs synthesized by acid-base addition contain the acid and base precursors in autoprotolysis equilibrium with the ionic pairs. 23 The particular combination of ions and neutral species determines the properties of the synthesized IL, and then its performance in an application is influenced by all the interactions that are established within the reactive system.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical techniques are being intensely used for exploiting the outstanding properties of ILs as electrolytes, 26 and particularly cyclic voltammetry has shown to be extremely useful as a detection technique for revealing the presence of free species other than the ionic pair. 21,23 Thus, in this work the monitoring of ILs by cyclic voltammetry was carried out in order to perceive the effect of the IL synthesis conditions and parameters (synthesis reaction time, purification steps) on the amounts of these species. Our hypothesis is that a specific behaviour of a sulfonic TSIL in a reactive system cannot be attributed solely to the presence of the SO 3 H groups that functionalize the TSIL structure.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to optimize the selection of TSIL to achieve a specific property and analyze the effect of the decoration of structure of imidazolium cation with a sulfonic group. In this direction, the synthesis of a TSIL was developed by decorating the structure of the 1butyl-3-methyl imidazolium (bmim) cation with an acid sulfonic group, to obtain 1-(4-sulfonic acid)butyl- 3 [4]. According to what was observed and in order to correlate results, the ILs were applied in two reactive systems: synthesis of dibenzoxanthenes and esterification reactions.…”
Section: Introductionmentioning
confidence: 99%